ANALISIS DAN PERANCANGAN SISTEM ANTRIAN TIKET DAN PENJADWALAN DOKTER DENGAN ALGORITMA FIRST IN FIRST OUT (FIFO) BERBASIS WEB (STUDI KASUS PUSKESMAS CIKUYA) - Ade Supriono; Sewaka (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Abstract− The development of an increasingly fast and dynamic era requires humans to live more quickly and efficiently in doing everything in life. In the process of service in the medical world, it is also required to provide fast and efficient services in providing services to the community. The system of queuing at the counter and scheduling of doctors is one of the most important things in the current era, considering that the world is currently facing the Covid-19 virus which has made the medical world quite overwhelmed in dealing with the virus. The existence of a policy to be able to keep a distance and stay away from crowds makes public service places, especially hospitals and health centers, must be able to implement health protocols. The problem in this study is that there are still a few crowds in the queue for treatment and the inefficient process of making queue tickets at the counter at the Cikasungka Health Center, this makes the application of health protocols neglected. Therefore, to overcome this problem, a web-based ticket queue and doctor scheduling system was designed. The method used in making the ticket queuing system and doctor scheduling is Waterfall which is used to analyze the design of the system to be made. The results of this study are in order to facilitate the process of making counter queues and scheduling doctors at the Cikasungka Public Health Center.